2012
DOI: 10.1136/bmjqs-2012-000942
|View full text |Cite
|
Sign up to set email alerts
|

In situ simulation: detection of safety threats and teamwork training in a high risk emergency department

Abstract: Objective Implement and demonstrate feasibility of in situ simulations to identify latent safety threats (LSTs) at a higher rate than labbased training, and reinforce teamwork training in a paediatric emergency department (ED). Methods Multidisciplinary healthcare providers responded to critical simulated patients in an urban ED during all shifts. Unannounced in situ simulations were limited to 10 min of simulation and 10 min of debriefing, and were video recorded. A standardised debriefing template was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
396
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(411 citation statements)
references
References 27 publications
8
396
0
7
Order By: Relevance
“…7,13-15 A randomized controlled study in the Netherlands demonstrated an improvement in team performance in obstetrical management after training in a simulation center. 16 In situ simulation allows a better identification of systems issues 8,9 or safety threats 10,17 and has been shown to improve the management of deteriorating patients. 18 In situ training is less developed than training in a simulation center probably because it is more difficult to organize particularly when…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,13-15 A randomized controlled study in the Netherlands demonstrated an improvement in team performance in obstetrical management after training in a simulation center. 16 In situ simulation allows a better identification of systems issues 8,9 or safety threats 10,17 and has been shown to improve the management of deteriorating patients. 18 In situ training is less developed than training in a simulation center probably because it is more difficult to organize particularly when…”
Section: Discussionmentioning
confidence: 99%
“…10 In situ training and evaluation was feasible in our network because the simulator and all the equipment could be transported in a regular car; moreover, all the maternities were located ,200 km from the organizing center. We could not evaluate whether such a program including almost all the staff members and performed in a simulation center over a short period would have produced the same results.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, simulations are becoming more widespread in medicine as an investigative tool. 44,45 Second, because the study was conducted in only 4 hospitals in 1 country, further research is required to assess the broad-scale generalizability of our findings. Third, despite evidence that the impact of rudeness is not conditioned according to source, 20,21 our findings may not be generalizable to rudeness stemming from other, nonauthority sources.…”
Section: Figurementioning
confidence: 99%
“…All participants were asked to complete a human factors questionnaire after each session. Facilitators then completed a latent threats review which covered the crisis resource management issues below: (Patterson et al, 2013). Simulation also offers the opportunity to formally debrief the members of the multiprofessional team, something that occurs rarely in practice, and has been shown to be the most important element in providing effective learning in simulation-based education.…”
Section: Ep222mentioning
confidence: 99%